Relationship between Ventilation, Light Intensity and Conditions for Water Reservoirs in the House with the Occurrence of Dengue Hemorrhagic Fever in Medan City in 2019 - Venny Melinda Nasmita; Nurmaini; Fazidah Aguslina Siregar (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
Dengue hemorrhagic fever is an infectious disease caused by dengue virus and is transmitted through the bite of the Aedes aegypti or Aedes albopictus mosquito. Ventilation and light intensity are physical controls to reduce the risk of outbreaks of DHF. Medan is one of the cities that is endemic for DHF, so DHF cases continue to occur and even increase every year. In 2018 cases of dengue hemorrhagic fever have increased as many as 1490 cases with a death rate of 13 people. This study aims to analyze the relationship between ventilation, light intensity and water storage conditions with the incidence of DHF. This type of research is descriptive, with case control design. The study population was 98 households, the study sample consisted of 49 cases and 49 controls. Data collection through observation and measurement. Data analysis methods include univariate analysis, bivariate analysis using chi square. The univariate analysis results demonstrated that the dengue hemorrhagic fever cases had higher prevalence rate in August (41%) and had dominant attack on 3-14 year old people (39%) as well as on females (59%). The bivariate analysis results indicated that lighting (OR= 9.474), ventilation (OR= 5.949) and condition of water reservoirs (OR= 4.769) were correlated with prevalence of dengue hemorrhagic fever. It was suggested to the public to pay attention to the intensity of light inside the house and install a wire mesh on the ventilation if the home environment contained a lot of DHF vectors and closed water reservoirs.